Zakat investment in Shariah - Gafoordeen, Nagoor; Mohamed Mohideen, Nayeem; Akbar, Mohamed Aslam (Medwell Journals, 2016)
Zakat is an obligatory payment and the idea of zakat investment was initiated by the belief that providing the poor and needy with a non-substantial amount of fund that is mostly used to pay for their expenditure is not enough to undertake poverty. Muslim intellectuals suggested a long-term measure involving the investment of zakat that not only complement the poor with a stream of income that is more consistent and continuous, but also provide a source of income to fund overall Muslim economic development. However, Muslim intellectuals found that investment of zakat may make the payment legally vulnerable from the Shariah (Islamic law) point of view. Thus, many fatwas and views have been expressed by the Muslim intellectuals as guidelines to ensure that the investment activities conform to Shariah. This study examines contemporary intellectuals’ viewpoints of zakat investment.